Hyperaggregability of Platelets in Thromboembolic Disorders - Yamazaki, Hiroh; Takahashi, Takeo; Sano, Tadahiro (Thrombosis and Haemostasis, 1975)
Platelet aggregability was measured using platelet rich plasma (PRP) collected from 197 clinical cases including 52 healthy volunteers. In 31 patients of acute stage of thrombosis (within 2 weeks from the onset), a significant enhancement of platelet aggregation measured 5 min after an addition of 3 and 10 μM ADP or 0.1 and 1 μg/ml of adrenaline to PRP (p < 0.05, compared to the healthy group). Also a significant enhancement of secondary aggregation induced by adrenaline was observed (p <0.05). The enhancement was especially marked in the response induced by adrenaline. Such an enhancement was not observed in patients in the recovery stage of thrombosis, hypertension, angina pectoris and other miscellaneous diseases. There was no difference in the parameters related to the velocity of aggregation or intensity of primary aggregation between the diseased and the healthy group. In response induced by collagen (bovine achules tendon, 0.3 and 1 mg/ml) any difference in the aggregation curve was not observed between the diseased and the healthy group. Such findings suggest a presence of an enhancement of ADP-release mechanism of platelets in acute thrombosis. Also a significance of adrenaline-induced platelet aggregation was proposed to detect platelet functions for analysis of mechanism of thromboembolic disorders.